Conversion And Storage Of Solar Energy Using Metal Complexes As Photocatalysts - Bhattacharyya, R. G. (Indian Science Cruiser, 1989)
Many metal compounds such as oxides, sulphides, selenides or tellurides, act as semiconductors, and suitable transition metal complexes behave as photosensitizers for photogalvanic or photoelctrochemical water splitting process, leading to production of dihydrogen, a fuel which will ultimately replace fossil fuels in future. Details of hydrogen production mechanism to be technically viable have been duscussed. J^he author and his collaborators working in this area have achieved a 4% solar energy efficiency in Photoelectrosynthetic hydrogen generation